New Generation of Sangkhalok Figurines - Semachai, Chanakarn (Journal of Urban Culture Research, 2025)
This research on the New Generation of Sangkhalok Figurines aims to investigate the history and craftsmanship of Sangkhalok production, highlighting its distinctive features to guide future developments. It seeks to collect contemporary concepts that resonate with today's audience by engaging the younger generation to establish set guidelines for creating figurines of the new generation. The study employs participatory learning theory, involving a group of Generation Z participants aged 8-15 from three schools. These participants designed figurines based on their ideas, which were then evaluated by experts to determine the best design principles. The refined designs are being incorporated into the local production process in preserving cultural significance, resulting in the creation of New Generation Sangkhalok figurines. These contemporary art pieces are deeply rooted in traditional wisdom, yet they also mirror contemporary lifestyles. They captivate the imagination of Gen Z, innocence, and artistic sensibilities.